Efficacy and safety of a novel hand dorsum intravenous indwelling needle fixation device in hospitalized pediatric patients: a retrospective controlled study - He, Wanling; Lu, Changchun; Qin, Qianyu; You, Yulin; Tan, Huiyi; Yao, Yiming; Guo, Shuaijie; Ling, Qian; Xu, Xinyi (Frontiers in Pediatrics, 2025)
BackgroundProper fixation of dorsal hand intravenous indwelling needles is a key component to ensure the smooth implementation of short-term intravenous therapy for pediatric inpatients. However, traditional fixation methods often face problems such as easy dislodgement and restriction of patient movement, which affect the safety and comfort of treatment. The aim of this study was to evaluate the efficacy and safety of a new dorsal hand intravenous indwelling needle fixation device in clinical applications and to analyze it retrospectively in comparison with traditional fixation methods.MethodsThis was a retrospective controlled study that included a total of 108 pediatric inpatients who were retrospectively divided into Group 1 (n = 55) and Group 2 (n = 53) based on the type of fixation they actually received. The Group 1 used a new type of fixation device for indwelling needle fixation, while the Group 2 used the traditional fixation method. The total number of indwelling needles used, the average length of time a single indwelling needle was left in place, the comfort score, the incidence of unplanned removal, and the incidence of medical adhesion-related skin injury were compared between the two groups during the hospitalization period.ResultsCompared with the traditional fixation method, the Group 1 with the new fixation device had a significant reduction in the total number of indwelling needles used during hospitalization (P = 1.079 × 10−15), and a significant prolongation of the average length of time a single indwelling needle was left in place (P = 3.136 × 10−7). Comfort was significantly improved (P = 0.0009), and both the unplanned removal rate and the medical adhesion-related skin injury incidence were significantly reduced (P = 6.738 × 10−5, P = 0.0003, respectively).ConclusionThe new dorsal hand intravenous needle fixation device can effectively reduce the number of needle changes during hospitalization, prolong the duration of its use, improve patient comfort, and significantly reduce the incidence of unplanned removal and medical adhesion-related skin injury, which has good clinical application value.